Transient pseudohypoaldosteronism in infancy mainly manifested as poor appetite and vomiting: Two case reports and review of the literature - Tuoheti, Yueerlanmu; Zheng, Yucan; Lu, Yan; Li, Mei; Jin, Yu (Frontiers in Pediatrics, 2022)
Introduction Transient Pseudohypoaldosteronism (TPHA) is a very rare condition usually secondary to urinary tract malformations (UTM) and/or urinary tract infection (UTI). It is characterized by hyperkalemia, hyponatremia, metabolic acidosis, and elevated plasma aldosterone levels. Given that the predominant manifestations of TPHA patients are digestive tract symptoms, such as poor appetite, vomiting, and weight gain, it is easily misdiagnosed as digestive tract diseases. Case reports Two children with poor appetite and vomiting were admitted to the Department of Gastroenterology, Children’s Hospital of Nanjing Medical University, from 2020 to 2021. Laboratory test results of these two children revealed hyponatremia (< 135.00 mmol/L), hyperkalemia (> 5.50 mmol/L), and hyperaldosteronism (> 180.00 ng/L). Moreover, genetic tests demonstrated no genetic variants highly associated with the phenotype in both cases. The two patients were subsequently treated with electrolyte correction. One of them also treated with antibiotics and one of them underwent surgery. They were followed for 8 and 4 months, respectively. No complications were observed during the follow-up period. This review aimed to outline both cases with parental consent. Conclusion Transient pseudohypoaldosteronism should be considered in children younger than 6 months, presenting with vomiting, poor appetite, unexplained hyponatremia, hyperkalemia, elevated aldosterone levels, and urethral malformation or urinary tract infection. Furthermore, attention should be paid to whether salt supplementation or anti-infection therapy is effective.